1982
DOI: 10.1159/000123410
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Stress Decreases Steroid Aromatase Activity in Brains of Male and Female Rat Fetuses

Abstract: Steroid aromatase activity was measured in homogenates of combined hypothalamic and amygdaloid specimens obtained from 17- to 21-day-old male and female rat fetuses. The fetuses were obtained both from normal mothers and mothers exposed to a regimen of stress that results in a failure of behavioral masculinization and defeminization of male offspring. Tissue samples from stressed mothers and controls were obtained during the dark phase of the day (Villanova group, days 17, 18, 19, 20 and 21 postconception). Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
0
2

Year Published

1986
1986
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(53 citation statements)
references
References 21 publications
5
46
0
2
Order By: Relevance
“…In the fetal rhesus monkey no sex difference in aromatase activity was found in the POA or hypothalamus, and neither gonadectomy nor androgen treatment affected aromatase activity suggesting that this activity was not regulated by circulating androgens (13). Similarly, in the rat, Weisz et al (22) found no sex difference in aromatase activity of combined hypothalamic and amygdaloid tissues across Days E 17 to E21. However, George and Ojeda (23) reported a trend where aromatase activity in the POA of rats was higher in male than female fetuses on Day E22.…”
Section: Discussionmentioning
confidence: 93%
“…In the fetal rhesus monkey no sex difference in aromatase activity was found in the POA or hypothalamus, and neither gonadectomy nor androgen treatment affected aromatase activity suggesting that this activity was not regulated by circulating androgens (13). Similarly, in the rat, Weisz et al (22) found no sex difference in aromatase activity of combined hypothalamic and amygdaloid tissues across Days E 17 to E21. However, George and Ojeda (23) reported a trend where aromatase activity in the POA of rats was higher in male than female fetuses on Day E22.…”
Section: Discussionmentioning
confidence: 93%
“…The extracts were dried, reconsti tuted in 50 pi of chloroform, and applied to TLC plastic sheets pre-coated with silica gel (Brinkmann Instr. Inc., Westbury, N.Y.) that were developed in solvent systems and processed as previously outlined [2,22]. The isolated aeetylated steroids were processed and an aliquot was assayed for 5 H/ 14C radioactivity of the 3H product produced from the conversion of the substrate ([ 1,2,6.7-3H]T), which has a majority oflabel on the (t-positions ( > 65%), was compared to the recovery of the ra dioactive MC' standard to calculate the rate of hypothalamic aromatase activity.…”
Section: Measurement O F Aromatase Activitymentioning
confidence: 99%
“…The chloroform phase from the tritiated water assay incubations was used to determine 5a-reductase activity for each sample, as previously described [2,23], In brief, an aliquot o f the chloroform phase was dried down with 10 pg each of androslenedione; T; DHT; 5«-androstane-3u, 17|)-diol; 5a-androstane-3, 17-dione; 5(S-RHT; 5|S-androstane-3, 17-dione; 5(5-androstane-3a, 17|l-diol: and 5f)-androstane-3p, I7|i-diol. The steroids were resolved on TLC plastic sheets using dichloro- …”
Section: Measurement O F Sa-reductase Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Brain aromatase activity (AA) appers first in the diencephalon at gestational day (GD) 15 in male and female rat fetus [9], at about the time of onset and further development of estrogen receptors in hypothalamus and preoptic area (POA). Enzyme activity reaches its peak at around G D I9 in male and female rat fetuses to decline gradually with age [10,11]. Data on perinatal sexual dimorphism of this enzyme are controversial.…”
mentioning
confidence: 99%